Evaluation of elastomeric models for engine mountings applications - Ladipo, Ismail; Darsivan, Fadly Jashi; Faris, Waleed Fekry (Inderscience Publishers, 2015)
The requirements of modern vehicle engine vibration isolation systems have been upgraded from the traditional passive mode to semi-active mode or active mode. With the relative advantages of semi-active mode over active mode and passive mode, the dynamic analysis of the behaviours of elastomers when used in the semi-active mode requires more attention. This research compares the use of a three-parameter classic model and a four- parameter model on the isolation performance of elastomers. Using an analytically developed mathematical model, the effect of modifying the classic three-parameter model will be shown in the simulation results of the transmissibility properties of elastomeric mounts. The results show higher vibration isolation effects using the four-parameter model. The four-parameter elastomeric mounts have higher damping characteristics which is needed for elastomeric mounts at resonance frequency. These results will be incorporated into the study of the effect of varying the dynamic performance of elastomers in future research.